Enhancing hydrogen storage properties of the Mg/MgH2 system by the addition of bis(tricyclohexylphosphine)nickel(II) dichloride. (3rd May 2019) - Galey, Basile; Auroux, Aline; Sabo-Etienne, Sylviane; Grellier, Mary; Postole, Georgeta
Abstract: This is a first report on the use of the bis(tricyclohexylphosphine)nickel (II) dichloride complex (abbreviated as NiPCy3) into MgH2 based hydrogen storage systems. Different composites were prepared by planetary ball-milling by doping MgH2 with (i) free tricyclohexylphosphine (PCy3) without or with nickel nanoparticles, (ii) different NiPCy3 contents (5–20 wt%) and (iii) nickel and iron nanoparticles with/without NiPCy3. The microstructural characterization of these composites before/after dehydrogenation was performed by TGA, XRD, NMR and SEM-EDX. Their hydrogen absorption/desorption kinetics were measured by TPD, DSC and PCT. All MgH2 composites showed much better dehydrogenation properties than the pure ball-milled MgH2 . The hydrogen absorption/release kinetics of the Mg/MgH2 system were significantly enhanced by doping with only 5 wt% of NiPCy3 (0.42 wt% Ni); the mixture desorbed H2 starting at 220 °C and absorbed 6.2 wt% of H2 in 5 min at 200 °C under 30 bars of hydrogen. This remarkable storage performance was not preserved upon cycling due to the complex decomposition during the dehydrogenation process. The hydrogen storage properties of NiPCy3-MgH2 were improved and stabilized by the addition of Ni and Fe nanoparticles. The formed system released hydrogen at temperatures below 200 °C, absorbed 4 wt% of H2 in less than 5 min at 100 °C, and presented good reversible hydriding/dehydriding cycles. A study of the different storage systems leads to the conclusion that the NiPCy3 complex acts by restricting the crystal size growth of Mg/MgH2, catalyzing the H2 release, and homogeneously dispersing nickel over the Mg/MgH2 surface. Graphical abstract: Image 1 Highlights: Highly efficient Mg/MgH2 storage system. Hydrogen sorption kinetics of MgH2 improved by C36 H66 Cl2 NiP2 doping. Complete reversibility achieved by addition of Ni and Fe nanoparticles. Onset of hydrogen desorption at a temperature of 175 °C. Absorption of 4 wt% of H2 in less than 5 min at 100 °C.